Effect of gamma irradiation on proliferation and growth of friable embryogenic callus and in vitro nodal cuttings of ugandan cassava genotypes - Apio, Hellen B.; Elegba, Wilfred; Nunekpeku, Wonder; Otu, Solomon Ayeboafo; Baguma, Julius Karubanga; Alicai, Titus; Danso, Kenneth Ellis; Bimpong, Isaac Kofi; Ogwok, Emmanuel (Frontiers in Plant Science, 2024)
Cassava (Manihot esculenta Crantz) production and productivity in Africa is affected by two viral diseases; cassava mosaic disease (CMD) and cassava brown streak disease (CBSD). Induced mutagenesis of totipotent/embryogenic tissues or in vitro plant material can lead to the generation of CMD and/or CBSDtolerant mutants. To massively produce non-chimeric plants timely and with less labour, totipotent cells or tissues are a pre-requisite. This study aimed to determine the effect of gamma radiation on the proliferation and growth of friable embryogenic callus (FEC) and in vitro nodal cuttings respectively. To obtain FEC, 2-6 mm sized leaf lobes of nine cassava genotypes were plated on Murashige and Skoog (MS) basal media supplemented with varying levels (37, 50, 70, 100) µM of picloram for production of organized embryogenic structures (OES). The OES of five cassava genotypes (Alado, CV-60444, NASE 3, NASE 13 and TME 204) were crushed and plated in Gresshoff and Doy (GD) basal media in combination with the amino acid tyrosine in varying concentrations for FEC production. FEC from five cassava genotypes and in vitro nodal cuttings of nine genotypes were irradiated using five different gamma doses (0, 5, 10, 15, 20 and 25 Gy) at a dose rate of 81Gy/hr. The lethal dose (LD)50 was determined using the number of roots produced and flow cytometry was done to determine the ploidy status of plants. The highest production of OES was noted in Alado across varying picloram concentrations, while TME 204 obtained the highest amount of FEC. The irradiated FEC gradually died and by 28 days post irradiation, FEC from all five cassava genotypes were lost. Conversely, the irradiated in vitro nodal cuttings survived and some produced roots, while others produced callus. The LD50 based on number of roots varied from genotype to genotype, but plants remained diploid post-irradiation. Accordingly, the effect of gamma irradiation on Ugandan cassava genotypes was genotype-dependent. This information is foundational for the use of in vitro tissues as target material for cassava mutation breeding.